Increased Erythrocyte Eicosapentaenoic Acid and Docosahexaenoic Acid Are Associated With Improved Attention and Behavior in Children With ADHD in a Randomized Controlled Three-Way Crossover Trial. (November 2015) - Milte, Catherine M.; Parletta, Natalie; Buckley, Jonathan D.; Coates, Alison M.; Young, Ross M.; Howe, Peter R. C.
Objective: To investigate effects of omega-3 polyunsaturated fatty acids (n-3 PUFA) docosahexaenoic acid (DHA) and eicosapentaenoic acid (EPA) on attention, literacy, and behavior in children with ADHD.Method: Ninety children were randomized to consume supplements high in EPA, DHA, or linoleic acid (control) for 4 months each in a crossover design. Erythrocyte fatty acids, attention, cognition, literacy, and Conners' Parent Rating Scales (CPRS) were measured at 0, 4, 8, 12 months.Results: Fifty-three children completed the treatment. Outcome measures showed no significant differences between the three treatments. However, in children with blood samples ( n = 76-46), increased erythrocyte EPA + DHA was associated with improved spelling ( r = .365, p < .001) and attention ( r = −.540, p < .001) and reduced oppositional behavior ( r = −.301, p < .003), hyperactivity ( r = −.310, p < .001), cognitive problems ( r = −.326, p < .001), Diagnostic and Statistical Manual of Mental Disorders (4th ed.; DSM-IV ) hyperactivity ( r = −.270, p = .002) and DSM-IV inattention ( r = −.343, p < .001).Conclusion: Increasing erythrocyte DHA and EPA via dietary supplementation may improve behavior, attention, and literacy in children with ADHD.